Fabrication of Free‐Standing Hybrid Composite High Capacity Cathodes for Li−S Batteries with Nickel Oxide Polysulfide Adsorbent - Cem Adalı; Hilal Günsel (ChemElectroChem)
Abstract This study focuses on enhancing lithium‐sulfur (Li−S) battery performance by using nickel(II) oxide (NiO), as polysulfide adsorbent to mitigate the shuttle effect. Polysulfides have been shown to effectively adsorb onto the hydrophilic surfaces of polar metal oxides and thus suppress this effect. In this work, a NiO – reduced Graphene Oxide/Sulfur (NiO‐rGO/S) hybrid composite paper was developed for use as a binder‐free, flexible cathode. The characterization of the composite films was done through Fourier transform infrared spectroscopy (FT‐IR), Raman spectroscopy, thermogravimetric analysis (TG), field emission gun scanning electron microscopy (FEG‐SEM), energy dispersive x‐ray spectroscopy (EDS) and x‐ray diffraction (XRD). To test adsorption of polysulfides by NiO, ultraviolet‐visible (UV‐Vis) spectroscopy was applied. Electrochemical performance tests of CR2032 cells were also conducted by cyclic voltammetry (CV), charge‐discharge tests, electrochemical impedance spectroscopy (EIS). The NiO‐rGO/S cathode, particularly the one containing 2 % NiO, exhibited remarkable performance. It delivered an initial discharge capacity of 1230 mAh g−1, maintaining 1029 mAh g−1 after 300 cycles, with a high capacity retention of 83.1 %. This suggests that the NiO‐rGO/S hybrid composite is a promising candidate for improving the efficiency and lifespan of Li−S batteries.